Vaccination with a combination of STING agonist-loaded lipid nanoparticles and CpG-ODNs protects against lung metastasis via the induction of CD11bhighCD27low memory-like NK cells - Alaa M. Khalifa; Takashi Nakamura; Yusuke Sato; Hideyoshi Harashima (Experimental Hematology & Oncology, 2024)
Abstract Background Natural killer (NK) cells are effective in attacking tumor cells that escape T cell attack. Memory NK cells are believed to function as potent effector cells in cancer immunotherapy. However, knowledge of their induction, identification, and potential in vivo is limited. Herein, we report on the induction and identification of memory-like NK cells via the action of a combination of a stimulator of interferon genes (STING) agonist loaded into lipid nanoparticles (STING-LNPs) and cytosine-phosphorothioate-guanine oligodeoxynucleotides (CpG-ODNs), and the potential of the inducted memory-like NK cells to prevent melanoma lung metastasis. Methods The antitumor effects of either the STING-LNPs, CpG-ODNs, or the combination therapy were evaluated using a B16-F10 lung metastasis model. The effect of the combined treatment was evaluated by measuring cytokine production. The induction of memory-like NK cells was demonstrated via flow cytometry and confirmed through their preventative effect. Results The combination of STING-LNPs and CpG-ODNs tended to enhance the production of interleukin 12 (IL-12) and IL-18, and exerted a therapeutic effect against B16-F10 lung metastasis. The combination therapy increased the population of CD11bhighCD27low NK cells. Although monotherapies failed to show preventative effects, the combination therapy induced a surprisingly strong preventative effect, which indicates that CD11bhighCD27low cells could be a phenotype of memory-like NK cells. Conclusion As far as could be ascertained, this is the first report of the in vivo induction, identification, and confirmation of a phenotype of the memory-like NK cells through a prophylactic effect via the use of an immunotherapeutic drug. Our findings provide novel insights into the in vivo induction of CD11bhighCD27low memory-like NK cells thus paving the way for the development of efficient immunotherapies. Graphical Abstract